GawaiDayak: Efforts to Preserve The Tradition of The Kantuk TribeRanyai Village, West Kalimantan Indonesia - SigitWidiyarto, DadangSunendar, Iskandarwassid, Sumiyadi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to describe what and how the GawaiDayak oral tradition was carried out in Ranyai Village, West Kalimantan, and to describe the supporting factors and efforts to preserve the GawaiDayak tradition in Ranyai Village, West Kalimantan. Qualitative research is carried out in order to be able to explain and analyze phenomena, events, social phenomena, group beliefs, and opinions of a person or society towards something. Data were collected through interviews, documentation and document analysis. The method of data analysis was the stages of data collection, data reduction, data display and conclusion drawing. The research results were that the GawaiDayak tradition was a tradition that contains divine values. The GawaiDayak tradition presents the KantukDayak tribe as human beings who are good at being grateful. The supporting factors of the GawaiDayak tradition could help the DayakGawai tradition continue to develop and be sustainable